Toolkit for youth participation in urban policies - URBACT Young Citizens' Project (2006)
Abstract: The Toolkit for Youth Participation in Urban Policies is the result of three years of work of an international network of city administrations all over Europe. The cities involved have tried out new ways to involve young people in processes of urban development and policy-making. The authors have evaluated these processes and - together with the practitioners and the young people from the participating cities - have developed a toolkit that summarizes the experiences made during these years. The cities involved were Liverpool, Belfast, Bristol, Sunderland, District of Easington (all UK), Misterbianco (Italy), Evosmos (Greece), Sabadell (Spain), Birkirkara (Malta) and Mazekiai (Lithuania). (DIPF/Orig.)